Regulatory Impact Assessment (RIA) and Actual Impact Assessment (EIA) as Institutions for Improving the Quality and Effectiveness of Normative Legal Acts - B. K. Medoeva (Теоретическая и прикладная юриспруденция)
The institutions of regulatory impact assessment (RIA) and evaluation of actual impact (EAI) contain deliberative procedures in the form of public consultations. Deliberative procedures serve as a basis for the legitimacy of legal norms, and legitimacy predetermines the effectiveness of norms. It is necessary to improve the process of public consultations, to overcome the existing problems. Institutions are options for forecasting and modeling in law. Improving the compilation of summary reports and conclusions in the framework of RIA and EAI will contribute to the quality of institutions. The importance of the categories of “purpose” and “goal-setting” in rulemaking in the context of synthesis reports is considered. The author formulates his own definition of RIA.